A novel technique for optimal integration of active steering and differential braking with estimation to improve vehicle directional stability. (September 2018) - Mirzaeinejad, Hossein; Mirzaei, Mehdi; Rafatnia, Sadra
Abstract: This study deals with the enhancement of directional stability of vehicle which turns with high speeds on various road conditions using integrated active steering and differential braking systems. In this respect, the minimum usage of intentional asymmetric braking force to compensate the drawbacks of active steering control with small reduction of vehicle longitudinal speed is desired. To this aim, a new optimal multivariable controller is analytically developed for integrated steering and braking systems based on the prediction of vehicle nonlinear responses. A fuzzy programming extracted from the nonlinear phase plane analysis is also used for managing the two control inputs in various driving conditions. With the proposed fuzzy programming, the weight factors of the control inputs are automatically tuned and softly changed. In order to simulate a real-world control system, some required information about the system states and parameters which cannot be directly measured, are estimated using the Unscented Kalman Filter (UKF). Finally, simulations studies are carried out using a validated vehicle model to show the effectiveness of the proposed integrated control system in the presence of model uncertainties and estimation errors. Highlights: Novel optimal integrated control for active steering and differential braking is proposed. Controller weights are automatically tuned by fuzzy logic for various conditions. Stability of integrated controller with uncertainty is proved in the sense of Lyapunov. The proposed controller is evaluated in the presence of Unscented Kalman Filter. Small intentional braking force is used to assist the steering control.